KEMAMPUAN KOGNITIF, AFEKTIF DAN PSIKOMOTORIK SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPA MENGGUNAKAN METODE INKUIRI - Nurul Apsari; Sastiawati Sastiawati (STKIP Melawi, 2021)
Abstract: The research objective was to determine the effect of the inquiry method on student’s cognitive, affective, and psychomotor abilities in science learning. This type of research is experimental research. The design used in this research is True Experimental Designs with the type of Pretest-Posttest Control Group Designs. The research sample consisted of 50 students. The research instruments were questions (cognitive) and observation sheets (affective and psychomotor). Student’s cognitive abilities in the experimental class showed a significant difference compared to the control class. Obtained L0 = 0.4049 (α = 0.05) with Ltable = 0.206 so that the data population is not normally distributed. Then performed a difference test using UMann-Wihitney obtained Utabel = 81 Ucount = 70 so that Ho is rejected and Ha is accepted. Affective ability obtained L0 = 0.2671 (α = 0.05) with Ltable = 0.206 so that the data population is not normally distributed. Performed the UMann-Whitney test obtained Utabel = 99 ˂ Ucount = 139 so that there is no difference in affective ability in the control and experimental classes. The normality test on psychomotor abilities obtained L0 = 0.4049 (α = 0.05) Ltable = 0.206 so that the data population was not normally distributed. Furthermore, the UMann-Whitney test was carried out, it was obtained Utabel = 99 Ucount = 89, it was concluded that there were differences in student’s psychomotor abilities in the control class and the experimental class.Keywords: cognitive, affective, psychomotor, inquiry Abstrak: Tujuan penelitian adalah mengetahui pengaruh metode inkuiri terhadap kemampuan kognitif, afektif, dan psikomotorik siswa pada pembelajaran IPA. Jenis penelitian ini adalah penelitian eksperimen. Desain yang digunakan dalam penelitian adalah True Experimental Designs dengan tipe Pretest-Posttest Control Group Designs. Sampel penelitian berjumlah 50 siswa. Instrumen penelitian adalah soal (kognitif) dan lembar observasi (afektif dan psikomotorik). Kemampuan kognitif siswa pada kelas eksperimen menunjukkan terdapat perbedaan yang signifikan dibandingkan kelas kontrol. Diperoleh L0 = 0,4049 (α = 0,05) dengan Ltabel = 0,206 sehingga populasi data berdistribusi tidak normal. Kemudian dilakukan uji perbedaan menggunakan UMann-Wihitney yaitu Utabel=81 Uhitung = 70 sehingga Ho ditolak dan Ha diterima. Kemampuan afektif diperoleh L0 = 0,2671 (α = 0,05) dengan Ltabel=0,206 sehingga populasi data berdistribusi tidak normal. Dilakukan uji UMann-Whitney (tingkat kepercayaan 95%) diperoleh Utabel = 99 ˂ Uhitung = 139 sehingga tidak ada perbedaan kemampuan afektif pada kelas kontrol dan eksperimen. Uji normalitas pada kemampuan psikomotorik diperoleh L0 = 0,4049 (α = 0,05) Ltabel = 0,206 sehingga populasi data berdistribusi tidak normal. Selanjutnya dilakukan uji UMann-Whitney diperoleh Utabel = 99 Uhitung = 89 disimpulkan terdapat perbedaan kemampuan psikomotorik siswa pada kelas kontrol dan kelas eksperimen.Kata Kunci: kognitif, afektif, psikomotorik, inkuiri